1981
DOI: 10.1007/bf00422403
|View full text |Cite
|
Sign up to set email alerts
|

Fluphenazine pharmacokinetics and therapeutic response

Abstract: We conducted a double-blind study of therapeutic outcome versus mean steady-state levels in 29 newly admitted schizophrenic and schizoaffective patients who were treated with a constant dose of fluphenazine HCI over a 2-week period. both an upper and lower end of the therapeutic window were suggested by three nonresponders whose plasma levels were above 2.8 ng per ml and by two nonresponders and one partial responder whose plasma levels were below 0.2 ng per ml. The mean terminal half-life of fluphenazine (+ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 32 publications
5
31
0
1
Order By: Relevance
“…Mavroidis et al (1984) found a curvilinear relationship between clinical response and plasma levels, with levels above 0.7 ng/ml being associated with a less favorable outcome when compared with lower levels. Dysken et al (1981) found that three patients who had fluphenazine levels greater than 2.8 ng/ml did poorly, which also suggested a curvili near relationship. The one patient in our study with a level of more than 2.8 (acutally 3.5 ng/ml) remained unrelapsed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Mavroidis et al (1984) found a curvilinear relationship between clinical response and plasma levels, with levels above 0.7 ng/ml being associated with a less favorable outcome when compared with lower levels. Dysken et al (1981) found that three patients who had fluphenazine levels greater than 2.8 ng/ml did poorly, which also suggested a curvili near relationship. The one patient in our study with a level of more than 2.8 (acutally 3.5 ng/ml) remained unrelapsed.…”
Section: Discussionmentioning
confidence: 94%
“…In a study of (oral) fluphenazine hydrochloride, Mavroidis and his coworkers (1984) found that the lowest level of fluphenazine detectable with their assay, 0.13 ng/ml, was within the therapeutic range. Dysken et al (1981) found that levels of fluphenazine above 0.2 ng/ml were effective. Since the level of sensitivity of our assay was 0.15 ng/ml, it is possible that we did not find a threshold because the lowest amount of fluphenazine detectable was within the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chotic drugs and clinical response (Dysken et al, 1981;Bolvig Hansen and Larsen, 1985;Van Putten er al., 1992) while no definite relationship could be found in other studies (Van Putten et al, 1981;Volavoka et al, 1992). Previously, we studied the steady-state serum kinetics of zotepine.…”
Section: Introductionmentioning
confidence: 98%
“…Steady state plasma levels of fluphenazine in patients are in the low ng/ml range whether the drug is administered orally (Dysken et al 1981 ;Harris et al 1982;Mavroidis et al 1984a, b: Hitzemann et al 1985 or by intramuscular injection (Curry et al 1979;Wiles and Gelder 1979;Harris et al 1982;Altamura et al 1985;Brown and Silva 1985;Chang et al 1985;Marder et al 1986a, b). Consequently, plasma levels of fluphenazine are even harder to measure than those of other phenothiazines and there are relatively few plasma level studies on this piperazine type phenothiazine antipsychotic agent.…”
mentioning
confidence: 99%